Pengembangan Mesin Pengupas Sabut Kelapa Menggunakan Metode Quality Function Deployment (QFD) Untuk Area Indragiri Hilir - Helmi Candra; Yohanes Yohanes; Satriardi Satriardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In this study the Quality Function Deployment (QFD) develoved to know satisfication of costumer by questionnaire. The objective of this study is to find materials and components coconut dehusking machine accordance with the wishes of society. From the results of the questionnaire, the desired parameters is spare part available on market and cheapest product. Selection of materials and components coconut de-husking is: Selection of cuting knife cone shaped with the number of blades 34 pieces. Selection of conductor knife plat shaped with a number of blades 18 pieces. Selection of an electric motor with a power of 1 HP and 1400 rpm rotation. Selection of sprocket-chain the selected is the number of chain 40 with a pitch of 12.70 mm. The shaft material used is AISI 1045 with diameter of 25.4 mm. Material steel plate the selected is mild steel with a thickness of 2 mm. Steel materials profi L the selected is mild steel with dimension 50x50 mm. Selection of materials and components coconut de husking selected based on the wishes and needs of society Indragiri Hilir.Keyword : QFD, customer need, Materials, Components